Evaluation of microbiological quality of raw milk, sour milk and traditional yoghurt samples from Ouagadougou, Burkina Faso - TANKOANO, Abel; KABORE, Donatien; SAVADOGO, Aly; SOMAKPE, Adama; Nadia, Fanou; COMPAORE-SEREME, Diarra; HOUNHOUIGAN, Joseph D.; SAWADOGO-LINGANI, Hagrétou (My University, 2016)
The present study was undertaken to investigate the microbiological quality of milk and traditional dairy products sold in Ouagadougou markets. Forty-five (45) samples of milk and dairy products such as raw milk, sour milk and traditional yoghurt were collected. The microbiological parameters analyzed were aerobic mesophilic bacteria (AMB), total coliforms (TC), thermotolerant coliforms (TTC), Staphylococcus aureus (S. aureus), lactic acid bacteria (LAB) and yeasts and moulds (YM). The coliforms bacteria were then purified and identified using API 20E system. The results indicate that traditional milk and dairy products sold in the markets are not conforms to microbiological standards. The dominant coliforms associated with the dairy products were Klebsiella spp, Enterobacter spp, and E. coli.
Keywords: Milk; traditional dairy products; microbiological quality; Ouagadougou